A spoonful of sugar [large type] : a nanny's story - Ashford, Brenda, 1921- (Center Point Large Print, 2013)
Brenda Ashford is the quintessential British nanny. Prim and proper, gentle and kind, she seems to have stepped straight out of Mary Poppins. For more than six decades, Nanny Brenda swaddled, diapered, dressed, played with, sang to, cooked for, and looked after more than one hundred children. From the pampered sons and daughters of lords ensconced in their grand estates, to tough East End evacuees during the war, Brenda taught countless little ones to be happy, healthy, and thoroughly well-bred. Knowing a career caring for children was her only calling in life, Brenda attended London's prestigious Norland Institute, famous for producing top-class nannies. It was a sign of privilege and taste for the children of the well-to-do to be seen being pushed in their Silver Cross prams by a Norland nanny -- recognizable by their crisp, starched black uniforms with white bib collars, and their flowing black capes lined with red silk. Sprinkled throughout with pearls of wisdom (children can never have too much love, and learn how to sew a button, for goodness' sake) this delightful memoir from Britain's oldest living nanny is practically perfect in every way.